THE RELATIONSHIP OF ADOLESCENT KNOWLEDGE LEVEL AND ATTITUDE ABOUT DRUGS WITH THE EVENT OF DRUGS USING IN KORONG PARAK JUA NAGARI LURAH AMPALU SUB-DISTRICT VII KOTO SUNGAI SARIK, PADANG PARIAMAN REGENCY - Aulia Asman, Liza, and Debby Sinthania (JOURNAL SCIENTIFIC OF MANDALIKA (JSM), 2021)
Drug abuse still threatens teenagers, even though Indonesia has committed to being drug-free. 19% of the number of teenagers in Indonesia, or about 14 thousand teenagers, are indicated to be drug users. It is indeed very difficult to prevent the use of drugs among students, because the circulation of drugs is also increasingly intense along with the development of drug production technology in Indonesia. Psychologically, teenagers are very unstable or easily influenced by things that are less profitable and even endanger themselves and their future, such as narcotics is very dangerous for teenagers who have fallen into using narcotics. Some cases in adolescents who have become drug addicts begin with their curiosity about drugs, but due to a shallow understanding of drugs they are more deceived by temporary benefits and do not understand the bad consequences in the future. Pariaman Police the number of drug and psychotropic users found 27 cases, which increased sharply from 8 cases to 19 cases. Meanwhile, in Kabupaten Padang Pariaman, drug users in their teens were also found, as many as 50 cases, 14 of which were teenagers. The research used in this research is descriptive analytic with cross sectional method. The population in this study were teenagers in Korong Parak Jua Nagari Lurah Ampalu District VII Koto Sungai Sarik Padang Pariaman Regency as many as 83 people. The sampling technique is total sampling. The results of this study found that there was a significant relationship between knowledge about drugs and drug use, and there was a significant relationship between attitudes about drugs and drug use in Korong Parak Jua Nagari Lurah Ampalu District VII Koto Sungai Sarik Padang Pariaman Regency. Lack of control over the social environment of teenagers is also one of the causes of teenagers trying to use drugs because they have the attitude that drugs are a symbol of today's youth association.